Electromagnetic signatures of strong-field gravity from accreting black-holes. Issue 1 (1st January 2022) - Karas, Vladimír; Zajaček, Michal; Kunneriath, Devaky; Dovčiak, Michal
Highlights: Observations help us to test General Relativity. New techniques allow us to obtain independent constraints on the realistic models. We review approaches to explore variety of electromagnetic radiation signatures. We focus on strong gravity polarimetry with the upcoming satellite missions. Abstract: Observations of galactic nuclei help us to test General Relativity. Whereas the No-hair Theorem states that classical, isolated black holes eventually settle to a stationary state that can be characterized by a small number of parameters, cosmic black holes are neither isolated nor steady. Instead, they interact with the environment and evolve on vastly different time-scales. Therefore, the astrophysically realistic models require more parameters, and their values likely change in time. New techniques are needed in order to allow us to obtain independent constraints on these additional parameters. In this context, non-electromagnetic messengers have emerged and a variety of novel electromagnetic observations is going to supplement traditional techniques in the near future. In this outline, we summarize several fruitful aspects of electromagnetic signatures from accretion disks in strong-gravity regime in the outlook of upcoming satellite missions and ground-based telescopes. As an interesting example, we mention a purely geometrical effect of polarization angle changes upon light propagation, which occurs near the black hole event horizon. Despite that only numerical simulations can capture the accretion process in a realistic manner, simplified toy-models and semi-analytical estimates are useful to understand complicated effects of strong gravity near the event horizon of a rotating black hole, and especially within the plunging region below the innermost stable circular orbit.